The Impact of the Oil and Gas Industry on the Socio-Cultural Life of Local Communities in Teluk Bintuni - Irman, Dede; Sandi, Renda (International Journal of Humanities, Law, and Politics, 2025)
This study examines the socio-cultural impacts of the oil and gas industry on indigenous communities in Teluk Bintuni, West Papua, with particular focus on the Tangguh LNG Project. Through a qualitative case study approach utilizing in-depth interviews, participant observation, and document analysis, the research investigates how industrial development affects traditional practices, social structures, and economic patterns among the Sebyar, Sumuri, Irarutu, and Wamesa tribes. The study reveals significant transformations in community dynamics, including a shift from subsistence-based to cash-based economies, weakening of traditional leadership structures, and declining cultural practices. While the oil and gas industry has brought improved infrastructure, employment opportunities, and access to modern services through Corporate Social Responsibility (CSR) programs, it has simultaneously contributed to cultural erosion, social tensions, and land rights disputes. The research identifies a notable decrease in traditional ceremonies, communal gatherings, and indigenous language usage, particularly among younger generations increasingly drawn to modern lifestyles. Analysis of economic impacts shows a marked transition in livelihood patterns, with traditional hunting and farming activities being replaced by industrial employment and related service sectors. The study also highlights challenges in implementing effective CSR programs, noting limited community participation in planning and execution phases. These findings emphasize the need for more inclusive development approaches that balance economic growth with cultural preservation. The research contributes to the broader understanding of industrialization's impact on indigenous communities and provides recommendations for policy makers, corporate entities, and community leaders to foster more sustainable and culturally sensitive development practices. The study suggests that future success in similar contexts depends on strengthening legal frameworks for indigenous rights protection, improving community participation in decision-making processes, and developing more effective models for cultural preservation alongside industrial development.